Odpowiedzi

2009-12-09T20:00:47+01:00
A) {3x+y=5
{2x-y=0
5x=5/:5
x=1
3+y=5/-3
y=2
x=1

b) {4x - 5y = -4/*3
{-2x + 3y = 1,1/*5
12x-15y=-12
-10x+15y=5,5
2x=-6,5/:2
x=-3,25

4(-3,25)-5y=-4
-13-5y=-4/+13
-5y=9/:(-5)
y=-9/5
y=-1,8
x=-3,25

c) 3x - 2y = -12/*(-5)
2x - 5y = -19/*2
-15x+10y=60
4x-10y=-38
-11x=22/:(-11)
x=-2
-6-2y=-12/+6
-2y=-6/:(-2)
y=3
x=-2

2009-12-09T20:00:49+01:00
A)

3x + y = 5
2x - y = 0

3x+2x+y-y=5
5x=5
x=1


3x + y = 5
3(1)+y=5
3+y=5
y=-3+5
y=2


x=1
y=2


b)

4x - 5y = -4
-2x + 3y = 1,1 /*(2)

4x - 5y = -4
-4x+6y= 2,2
4x-4x-5y+6y= -4+2,2
y= 1,8


4x - 5y = -4
x-5(1,8)=-4
x-9=-4
x=9-4
x=5

x=5
y=1,8

c)

3x - 2y = -12 / *2
2x - 5y = -19 /* (-3)

6x-4y=-24
-6x+15y=57

6x-6x-4y+15y=-24+57
11y=33
y=3


3x - 2y = -12
3x- 2(3)= -12
3x-6= -12
3x=6-12
3x=-6 /3
x= -2

x=-2
y=3














2009-12-09T20:01:30+01:00
A)

3x + y = 5
2x - y = 0
czyli 5X =5 ; x=1
b)

4x - 5y = -4
-2x + 3y = 1,1 /2
4x - 5y = -4
-4x+6y =2,2
czyli y= -1,8
c)

3x - 2y = -12
2x - 5y = -19 / -3/2
3x -2y =-12
-3x +15/2y =57/2
5i1/2y=28i1/2
y =57/11